Biomechanical and physiological characterisation of four cycling positions - Swanton, A.; Shafat, A.; Anderson, R. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This study examined the effect of a change in body position on a selection of biomechanical and physiological variables affecting triathlon performance. Ten local triathletes, participated in this investigation. This study also introduces a novel, inexpensive method of calculating frontal projection area (FPA). FPA decreased a total of 31.6% as the athletes moved from the hoods position to the superman position. No changes in physiological performance variables were reported across the cycling positions. The superman position was found to elicit detrimental effects on peak sprint power output and body comfort. This data lends to the conclusion that the superman position does not offer a greater advantage to the triathlete.